An Arabidopsis ATPase gene involved in nematode‐induced syncytium development and abiotic stress responses. (16th April 2013) - Ali, Muhammad Amjad; Plattner, Stephan; Radakovic, Zoran; Wieczorek, Krzysztof; Elashry, Abdelnaser; Grundler, Florian M.W.; Ammelburg, Moritz; Siddique, Shahid; Bohlmann, Holger
Summary: The beet cyst nematode Heterodera schachtii induces syncytia in the roots of Arabidopsis thaliana, which are its only nutrient source. One gene, At1g64110, that is strongly up‐regulated in syncytia as shown by RT‐PCR, quantitative RT‐PCR, in situ RT‐PCR and promoter::GUS lines, encodes an AAA+‐type ATPase. Expression of two related genes in syncytia, At4g28000 and At5g52882, was not detected or not different from control root segments. Using amiRNA lines and T‐DNA mutants, we show that At1g64110 is important for syncytium and nematode development. At1g64110 was also inducible by wounding, jasmonic acid, salicylic acid, heat and cold, as well as drought, sodium chloride, abscisic acid and mannitol, indicating involvement of this gene in abiotic stress responses. We confirmed this using two T‐DNA mutants that were more sensitive to abscisic acid and sodium chloride during seed germination and root growth. These mutants also developed significantly smaller roots in response to abscisic acid and sodium chloride. An in silico analysis showed that ATPase At1g64110 (and also At4g28000 and At5g52882) belong to the 'meiotic clade' of AAA proteins that includes proteins such as Vps4, katanin, spastin and MSP1.